A Study on the Collaborative Development Path of Technological and Financial Innovation in Guangdong-Hong Kong-Macao Greater Bay Area - Liu Chengcheng (SHS Web of Conferences, 2024)
Strengthening the synergistic development of science and technology finance in the Guangdong-Hong Kong-Macao Greater Bay Area (GBA) is of great significance in further promoting financial liberalization and innovation, and deepening the financial co-operation and development between the Mainland, Hong Kong and Macao. In view of the positioning and mission of the GBA, there are still a lot of areas that need to be strengthened in the synergistic development of science and technology finance among the three places. For example, there is no synergy in regional science and technology co-operation and innovation, such as differences in institutional systems, lack of science and technology and financial talents, lack of mechanisms for circulation and sharing of innovative resources, and uneven distribution of innovative advantages. Based on this, GBA needs to build a unified and efficient platform for collaborative innovation and vigorously promote the circulation of resources; strengthen innovation cooperation and cultivate a strategic engine to lead industrial development; and focus on industrial upgrading and promote institutional innovation to form a new pattern of science and technology financial cooperation.